PEMBENTUKAN PENGADILAN TINDAK PIDANA KORUPSI BERDASARKAN UU NOMOR 31 TAHUN 1999 JUNCTO DAN UU NOMOR 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Triadi, Triadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Cooperation is carried out based on the provisions of the legislation in force or based on international agreements that have been recognized by the government. The Corruption Eradication Commission has the authority to coordinate and control the investigation, investigation and prosecution of corruption. The procedure for investigating Corruption in the Corruption Eradication Commission is determined in Article 43 and Article 44 of Law No. 30 of 2002. In this Article states that investigators who carry out investigations are investigators appointed by the Corruption Eradication Commission. Investigators here only carry out the function of investigating criminal acts of corruption. If the investigator in conducting an investigation finds sufficient preliminary evidence of an alleged criminal act of corruption, within no later than 7 (seven) working days from the date the sufficient preliminary evidence is found, the investigator may report to the Corruption Eradication Commission.